KAJIAN KEBIJAKAN PEMERINTAH TERHADAP HARGA PROPERTI PERUMAHAN DI PERKOTAAN - DWI JATI LESTARININGSIH; BASUKI BASUKI (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2015)
An urban population tended to increase from time to time as a result theconcentration of employment and urbanization . The population growthincreasing the needs of housing in urban areas. This research assessing thegovernment policies that can affect property prices housing in 10 big cities inIndonesia.The data presented in the form of secondary obtained from Bank Indonesia andBPS that published online. Data collection by searching internet . Data analysisuses simulation method by time series data using 10 cities at 2003-2010 withEviews program. `The results of research shows that the political conditions and global finansialcrisis occurring in a period of 2003-2010 affect residential property housingprices. Monetary policy by the government in terms of interest rates and inflationresponded by positive and negative in property housing market. The elasticity ofper capita income the inhabitants of large more high from the small town . ` Inthis case the of highest elasticity is Jabodebek and Surabaya .On the upcoming research expected to enter technical factors and managementsuch as: design, quality, number of rooms, buildings age and wide spaces with afield survey.Key words : government regulation, housing property, pemerintah, jokowi, berita ,joko widodo